Inflammatory mediators act at renal pericytes to elicit contraction of vasa recta and reduce pericyte density along the kidney medullary vascular network - Lilley, Rebecca J.; Taylor, Kirsti D.; Wildman, Scott S. P.; Peppiatt-Wildman, Claire M. (Frontiers in Physiology, 2023)
Regardless of initiating cause, renal injury promotes a potent pro-inflammatory environment in the outer medulla and a concomitant sustained decrease in medullary blood flow (MBF). This decline in MBF is believed to be one of the critical events in the pathogenesis of acute kidney injury (AKI), yet the precise cellular mechanism underlying this are still to be fully elucidated. MBF is regulated by contractile pericyte cells that reside on the descending vasa recta (DVR) capillaries, which are the primary source of blood flow to the medulla. Using the rat and murine live kidney slice models, we sought to investigate the acute effects of key medullary inflammatory mediators TNF-α, IL-1β, IL-33, IL-18, C3a and C5a on vasa recta pericytes. Live kidney slices taken from both mice and rats and exposed to TNF-α, IL-18, IL-33, and C5a demonstrated a real-time pericyte-mediated constriction of DVR. When pro-inflammatory mediators were applied in the presence of the AT1-R blocker Losartan the inflammatory mediator-mediated constriction that had previously been observed was significantly attenuated. When live kidney slices were exposed to inflammatory mediators for 4-hours, we noted a significant reduction in the number of NG2+ positive pericytes along vasa recta capillaries in both rat and murine kidney slices. Data collected in this study demonstrate that inflammatory mediators can dysregulate pericytes to constrict DVR diameter and reduce the density of pericytes along vasa recta vessels, further diminishing the regulatory capacity of the capillary network. We postulate that preliminary findings here suggest pericytes play a role in AKI.